Assessment of factors influencing the elution of chromium from ferrochromium slag using factorial design of experiment. (2021) - Sekhar Biswal, Sudhansu; Panda, Chittaranjan; Sahoo, Sudarsan; Jena, Trilochan; Chandra Panda, Kishor
Abstract: The solid waste material ferrochromium slag from the metallurgical industries encounters with disposal problem because of the presence of chromium. From the chemical composition study, the waste slag was observed to contain sizeable amount of environmentally harmful residual chromium. Chromium speciation in the slag was observed to exist as mostly immobile trivalent state. But there may be possibility of its conversion to leachable hexavalent chromium and its subsequent release from slag matrix causing chromium pollution problems. Elution of chromium from slag was studied under adverse environmental situations. The importance of factors influencing chromium elution from the slag samples were assessed using full factorial design analysis and accordingly regression equations were developed for elution of both hexavalent and total chromium. The significant physico-chemical factors affecting elution of chromium from slag matrix are obtained to be pH, size of particle, time of contact and their combinations.